SIMULTANEOUS QUANTIFICATION OF TAMOXIFEN AND 4-HYDROXY-N-DESMETHYLTAMOXIFEN LEVELS IN HUMAN PLASMA BY LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY: DEVELOPMENT AND APPLICATION IN BREAST CANCER PATIENTS - Harahap, Yahdiana; Leony, Nathania; Silalahi, Letare Merry Chresia; Andalusia, Rizka (International Journal of Applied Pharmaceutics, 2018)
Objective: This study was aimed to develop a highly sensitive and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the simultaneous quantification of tamoxifen, endoxifen, and clomiphene (internal standard) levels in human plasma. Methods: Plasma samples from 40 patients with breast cancer were prepared through liquid–liquid extraction in ethyl acetate, and chromatographic separation was performed on an Acquity UPLC BEH C18 column (1.7 μm, 2.1 mm×100 mm). The sample was eluted within 6.50 min at a flow rate of 0.200 ml/min under a gradient of 0.2% formic acid and acetonitrile. The analytes were then quantified through triple quadrupole MS with electrospray ionization in the positive ion mode and multiple reaction monitoring. Results: The method was successfully used to quantify the plasma levels of tamoxifen and endoxifen, yielding respective measurement ranges of 42.19–249.23 ng/ml and 1.52–26.62 ng/ml. Overall, this detection method was sensitive, with lower limits of quantitation of 0.625 ng/ml for tamoxifen and 0.125 ng/ml for endoxifen. In addition, this method was precise and accurate, with a between-run variation range of 5.19–12.38% and %diff range of −10.82%–+13.10%. Conclusion: This method demonstrated that approximately 80% of patients had plasma levels of endoxifen exceeding the expected clinical threshold (5.9 ng/ml). This rapid and simple method could be used to monitor tamoxifen metabolism and adjust doses as needed to achieve maximum effectiveness.